Left ventricular hypertrophy (LVH) in different stages of chronic kidney disease (CKD) patients and its correlation with anaemia - Tahara, Omma; Dutta, Pradip Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background : Chronic kidney disease (CKD) is a public health problem that increases the risk of cardiovascular morbidity and mortality. Heart failure with preserved ejection fraction characterized by left ventricular hypertrophy (LVH) and diastolic dysfunction is a common cardiovascular complication of CKD. Anaemia is present in both dialysis & non dialysis CKD patients. Anaemia causes left ventricular hypertrophy (LVH) which in turn leads to increases morbidity and mortality in CKD, even before progression of chronic kidney disease (CKD) to end stage renal disease (ESRD). Our study is aimed at to evaluate the prevalence of left ventricular hypertrophy (LVH) and its correlation with anaemia in hospitalized CKD patients. Materials and Methods : A cross-sectional study was done on 50 patients of different stages of CKD admitted in the chittagong medical college hospital (CMCH). All the clinical data were reviewed and recorded. Data was analyzed by SPSS-18 and p value <0.05 was considered statistically significant. Results : Majority of study population 64% was male, 36% was female. Most of the male patient (40%) of the study population were having abnormal left ventricular mass index (>130 gm/m2). More patients with severe left ventricular hypertrophy were found in stage 5 of CKD in female and male which was 8 and 23 respectively. Regarding correlation of Hb% with LVMI there was a significant negative correlation was found (r= -0.420, p = 0.003) between them means if Hb% decreases LVMI level increases. It was also found in male and female patients separately ( for male r = -0.778, p = 0.001 and for female r = -0.746, p = 0.001). Conclusion : Anemia is widely prevalent in our CKD patients. Severity of anemia is correlated to left ventricular hypertrophy in these patients. Hence correction of anemia early in these group of patients can halt or prevent cardiovascular morbidity and mortality. J Bangladesh Coll Phys Surg 2024; 42: 25-30